Timing and Prosody of Lexical Repetition: How Repeated Instructions Assist Visually Impaired Athletes' Navigation in Sport Climbing. Issue 4 (2nd October 2021) - Simone, Monica; Galatolo, Renata
ABSTRACT: How can lexical repetition help in guiding someone to do something? We take the example of sports climbing. Climbing demands complex bodily movements to reach holds and propel the body upwards. It is harder for visually impaired athletes, since they cannot see in advance where holds are located, so guides help them. There is a great deal of interplay between the (a) affordances of the climbing wall; (b) the guides' understanding of what the climbers are touching; and (c) the formatting, timing, and delivery of their instructions. We find that guides use carefully timed and prosodically calibrated lexical repetition (for example, up up up! ) to adjust both the duration and direction of the climbers' ongoing movements and to make sure that they get to their planned holds. Data are in Italian with English translation.